2013
DOI: 10.1109/map.2013.6735528
|View full text |Cite
|
Sign up to set email alerts
|

The Cavity Magnetron: Not Just a British Invention [Historical Corner]

Abstract: It is a common belief by many people that the resonant-cavity magnetron was invented in February 1940 by Randall and Boot from Birmingham University. In reality, this is not the full story. Rather, it is a point of view mostly advocated by the winners of the Second World War, who gained a great benefi t from this microwave power tube (thanks to a two-orders-of-magnitude increase of power) in the Battle of the Atlantic, in night bombing until the fi nal collapse of the German Reich, and in many other operations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 13 publications
0
18
0
Order By: Relevance
“…A mathematical formulation of the problem in Multi-CAO is as follows: ( 1 ) where denotes the desired covariance matrix of X for all possible lags and N the number of independent complex samples. For more details, see [14] [18].…”
Section: Sidelobes Suppression Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…A mathematical formulation of the problem in Multi-CAO is as follows: ( 1 ) where denotes the desired covariance matrix of X for all possible lags and N the number of independent complex samples. For more details, see [14] [18].…”
Section: Sidelobes Suppression Algorithmmentioning
confidence: 99%
“…The reason for one waveform to be used instead of another should be principally related to the application with the available equipment (e. g. transmitter) being a secondary consideration. This has not been the case with many legacy radar systems, for example the widely used, cheap and effective transmitters based on resonant cavity magnetron oscillators [1] are intrinsically unable to provide any modulation of the pulse and have poor spectral efficiency. These short pulses do however provide a simple way to avoid the well-known masking effect [2] and mutual interference problems [3].…”
Section: Introductionmentioning
confidence: 99%
“…d) There is a continuing interest, shown by meetings and publications, on the historical development of radar techniques and technologies, for example: MTI, Airborne Radar, Transmitters (with the wartime Tracking Radar (starting with the Würzburg [7], [10]), Bistatic and Passive Radar (starting from Klein Heidelberg, [8] and its References), Magnetron and its ancestors ( [9] and its References), Pulse Compression (and related technologies : dispersive delay circuits, SAW compressor/expanders…. ), Phased Array Radar, Adaptive Arrays (starting with the early Side Lobe Canceller, the MSLC…), etc.…”
Section: The Literature -Need For Updating and Completionmentioning
confidence: 99%
“…Magnetrons are microwave oscillators that are used extensively for commercial and military applications. They were produced in the early 1920's and helped lead the allies to victory in WWII with the implementation in radar systems [1]. Today, almost every household and even dorm room has one to rapidly cook food.…”
Section: Motivationmentioning
confidence: 99%
“…In 1917, Albert W. Hull, at General Electric (GE), proposed to use a magnetic field instead of an electric field to control the electric current in a valve. This was an attempt to circumvent the famous Lee de Forest's triode patent [1]. GE found that it would be easier to buy the patent and thus led to the term "magnetron" which was coined in a 1921 paper [17].…”
Section: Historymentioning
confidence: 99%